2016
DOI: 10.1007/s40653-016-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Deaf Trauma Survivors’ Experiences: Early Traumas Unique to Being Deaf in a Hearing World

Abstract: Conducting semi-structured American Sign Language interviews with 17 Deaf trauma survivors, this pilot study explored Deaf individuals’ trauma experiences and whether these experiences generally align with trauma in the hearing population. Most commonly reported traumas were physical assault, sudden unexpected deaths, and “other” very stressful events. Although some “other” events overlap with traumas in the general population, many are unique to Deaf people (e.g., corporal punishment at oral/aural school if c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
(18 reference statements)
0
13
2
Order By: Relevance
“…In contrast to our results, though, prior studies find that delayed access to language has broad cognitive effects 77,78 , including delayed development of language comprehension and production [79][80][81][82] , literacy 83,84 , and executive functions 85 , differences in language-related brain development [86][87][88] , and consequences for mental health 89,90 . This discrepancy is likely related to characteristics of our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, though, prior studies find that delayed access to language has broad cognitive effects 77,78 , including delayed development of language comprehension and production [79][80][81][82] , literacy 83,84 , and executive functions 85 , differences in language-related brain development [86][87][88] , and consequences for mental health 89,90 . This discrepancy is likely related to characteristics of our sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, in native signing children and all adults, the RTPJ showed selective responses to stories that described mental states (Mental condition; "The pirate thought that a pile of gold was buried behind Jimmy's house"), with low responses to Social stories that described people's physical appearance or enduring relationships, but not their mental states (Social condition; "Sarah and Lori play together on the soccer team"). In contrast to our results, though, prior studies find that delayed access to language has broad cognitive effects 77,78 , including delayed development of language comprehension and production 79-81 , 82 , literacy 83,84 , and executive functions 85 , differences in language-related brain development [86][87][88] , and consequences for mental health 89,90 . This discrepancy is likely related to characteristics of our sample.…”
contrasting
confidence: 99%
“…A study of 120 oral (speech-only) deaf children suggested that those children with the least developed language abilities had significantly more behavior problems than their hearing peers [68]. Elevated rates of emotional problems and disorders [33] and interpersonal trauma exposure [31,32,34,57] are present, and may have a relationship with language ability [70]. A relationship between language and behavioral health psychopathology appears evident in the deaf population.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a community sample of 308 deaf individuals found elevated reports of lifetime emotional abuse (27.5%), physical abuse (21.0%), and sexual violence (20.8%) [32]. Deaf adolescents can experience emotional and behavioral mental health problems associated with low self-esteem and peer rejection [33], and a range of developmental adversities unique to being deaf in a hearing world such as lack of accessible communication with parents and peers [34]. …”
Section: Behavioral Healthmentioning
confidence: 99%